2021
DOI: 10.3389/fpsyg.2021.566753
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Covid-19 Storm: A Web-Based Survey of Psychological Distress Among People Living in Lombardy

Abstract: In March 2020, the World Health Organization announced the Covid-19 outbreak a pandemic and restrictive measures were enacted by the Governments to fight the spread of the virus. In Italy, these measures included a nationwide lockdown, with limited exceptions including grocery shopping, certain work activities, and healthcare. Consistently with findings from previous studies investigating the psychological impact of similar pandemics [e.g., Severe Acute Respiratory Syndrome (SARS)], there is evidence that Covi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(25 reference statements)
1
13
2
Order By: Relevance
“…Our finding that female respondents were less distressed than male respondents may reflect sample bias towards more distressed males participating in the study, as typically distress in GI conditions is higher in females (Greuter et al, 2020 ). In addition, our study showed lower distress among younger people relative to older participants, which contrasts with pandemic research in the general population (Msherghi et al, 2021 ; Saita et al, 2021 ). While a previous smaller IBD-related study documented greater distress among young people in a younger sample (Cheema et al, 2021 ), we propose that our current findings could be interpreted as reasonable given a likely higher number of co-morbidities, polypharmacy, and greater hesitation to utilise technology as a means to maintain social networks.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that female respondents were less distressed than male respondents may reflect sample bias towards more distressed males participating in the study, as typically distress in GI conditions is higher in females (Greuter et al, 2020 ). In addition, our study showed lower distress among younger people relative to older participants, which contrasts with pandemic research in the general population (Msherghi et al, 2021 ; Saita et al, 2021 ). While a previous smaller IBD-related study documented greater distress among young people in a younger sample (Cheema et al, 2021 ), we propose that our current findings could be interpreted as reasonable given a likely higher number of co-morbidities, polypharmacy, and greater hesitation to utilise technology as a means to maintain social networks.…”
Section: Discussioncontrasting
confidence: 99%
“…The choice to focus on students was dictated by the observation that this group is among the most exposed to the pandemic risks. Saita, Facchin, Pagnini, & Molgora, ( 2021 ) found that students were more distressed than other groups with higher anxiety, depression, and perceived stress. In this regard, the uncertainty related to the sudden, unexpected transition to distance learning, and concerns about the future (Sahu, 2020 ) might have played an important role, with negative effects on the psychological health of this younger subgroup of people (Saita et al, 2021 ).…”
Section: Present Studymentioning
confidence: 99%
“…Thinking flexibly and positively about these challenges does not mean to deny the stressful and perhaps depressive aspects of the outbreak, as already identified by other studies (Saita et al, 2021 ). Participants expressed their need to share emotions, in the search for recognition and acceptance.…”
Section: Discussionmentioning
confidence: 57%